Characterization of S-nitrosoglutathione reductase from Brassica and Lactuca spp. and its modulation during plant development - Tichá, Tereza; Činčalová, Lucie; Kopečný, David; Sedlářová, Michaela; Kopečná, Martina; Luhová, Lenka; Petřivalský, Marek (Nitric oxide, 2017)
Cellular homeostasis of S-nitrosoglutathione (GSNO), a major cache of nitric oxide bioactivity in plants, is controlled by the NADH-dependent S-nitrosoglutathione reductase (GSNOR) belonging to the family of class III alcohol dehydrogenases (EC 1.1.1.1). GSNOR is a key regulator of S-nitrosothiol metabolism and is involved in plant responses to abiotic and biotic stresses. This study was focused on GSNOR from two important crop plants, cauliflower (Brassica oleracea var. botrytis, BoGSNOR) and lettuce (Lactuca sativa, LsGSNOR). Both purified recombinant GSNORs were characterized in vitro and found to exists as dimers, exhibit high thermal stability and substrate preference towards GSNO, although both enzymes have dehydrogenase activity with a broad range of long-chain alcohols and ω-hydroxy fatty acids in presence of NAD+. Data on enzyme affinities to their cofactors NADH and NAD+ obtained by isothermal titration calorimetry suggest the high affinity to NADH might underline the GSNOR capacity to function in the intracellular environment. GSNOR activity and gene expression peak during early developmental stages of lettuce and cauliflower at 20 and 30 days after germination, respectively. GSNOR activity was also measured in four other Lactuca spp. genotypes with different degree of resistance to biotrophic pathogen Bremia lactucae. Higher GSNOR activities were found in non-infected plants of susceptible genotypes L. sativa UCDM2 and L. serriola as compared to resistant genotypes. GSNOR and GSNO were localized by confocal laser scanning microscopy in vascular bundles and in epidermal and parenchymal cells of leaf cross-sections. The presented results bring new insight in the role of GSNOR in the regulation of S-nitrosothiol levels in plant growth and development.
Keywords: salát (hlávkový); Plant Development; aldehydoxidoreduktasy; Lactuca; genotyp; Brassica; vývoj rostlin; Oxidoreductases; Genotype; oxidoreduktasy; Aldehyde Oxidoreductases